Digital customer experience engineering : strategies for creating effective digital experiences - Wiedenhoefer, Lars (Apress, 2021)
Customer experience engineering applied to the engineering department is rare, but needed. Most companies keep support, UX, engineering, product, and CX separate. To address this gap, this book highlights roles and techniques that are proven to accelerate issue detection and prevention by 30% or more. With the author's vast experience in tech support, he has developed techniques and skills that allow engineers to gain customer insights faster and through new and insightful sources that are within their reach. You will develop a deep understanding of the impact of issues; understand and optimize the speed of the engineering feedback loop (issue resolution time); and develop the ability to calculate the cost of the issues or customer friction to the business (in aggregate and on a case-by-case basis). Organizations can save significant money and add additional revenue by addressing customer friction proactively in collaboration with product, engineering, and site reliability engineering (SRE) functions and reduce the average time of an issue resolution by 80%. The cross-functional leadership, mentoring, and engineering techniques you'll learn from this proactive stance are very valuable and teachable, and this book will show you the path forward.